Green philosophies and messages in contemporary Indonesian short stories - Rawson, David (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2023)
Economic development and environmental stories are rarely out of the press including the Indonesia press and provide warnings of mankind’s growing demands and impact on the environment. In Indonesia, media publications report on a wide range of economic development activities expected to generate higher economic growth and greater prosperity. Less prominence is given to the negative impacts of economic development on the environment and people. In Indonesian newspapers, there are also short stories which explore this economic and environmental relationship. Literary works can challenge the mainstream perception of this relationship which focuses on the economic. In these works, we see the political and economic relationships between groups and their different relationships with the environments. Differences which can lead to conflict, inequality, and poor environmental outcomes. Literary works, in this paper, short stories, not only present these complex relationships in interesting and novel ways but also contain a philosophy about these relationships. This paper takes a sample of twelve short stories published over the period 1970 to 2022 to examine this relationship. It draws upon the theory of narratology (Bal 2017) to analyse points of view (‘focalisations’), Gramsci’s (1999) concept of philosophy, and de Geus’s (1999) concept of green philosophy and literature. This paper finds the dominant group’s type of economic development-environmental relationship is characterised by a commodification of the subaltern and the environment. The subaltern in contrast seek to conserve traditional ways and their relationship with the environment. Elements of a green philosophy are grounded in traditional beliefs of respect for nature with a message of creating awareness of the disempowerment of the subaltern.